2020
DOI: 10.1186/s12936-020-03160-5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of antibody responses to Plasmodium falciparum antigens in individuals differentially exposed to Anopheles bites

Abstract: Background: In malaria-endemic areas, human populations are frequently exposed to immunomodulatory salivary components injected during mosquito blood feeding. The consequences on pathogen-specific immune responses are not well known. This study evaluated and compared the humoral responses specific to merozoite stage vaccine candidates of Plasmodium falciparum, in children differentially exposed to Anopheles bites in a natural setting. Methods:The cross-sectional study was carried out in Bouaké (Côte d'Ivoire) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…In the present study, we showed that Aedes exposure was negatively associated with the anti- Pf GLURP-R0 immune response, whereas it was positively associated with the anti- Pf Schz IgG response. The epidemiological observation for the down-regulated IgG response to Pf GLURP-R0 in individuals with higher exposure is consistent with previous studies that reported a down-regulated immune response to a specific antigen in hosts exposed to arthropod saliva compared with naive vertebrate hosts [ 21 , 32 , 33 ]. Schizonts comprise a set of antigens with varying immunogenicity, while Pf GLURP-R0 is a unique antigen at the surface of infected erythrocytes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, we showed that Aedes exposure was negatively associated with the anti- Pf GLURP-R0 immune response, whereas it was positively associated with the anti- Pf Schz IgG response. The epidemiological observation for the down-regulated IgG response to Pf GLURP-R0 in individuals with higher exposure is consistent with previous studies that reported a down-regulated immune response to a specific antigen in hosts exposed to arthropod saliva compared with naive vertebrate hosts [ 21 , 32 , 33 ]. Schizonts comprise a set of antigens with varying immunogenicity, while Pf GLURP-R0 is a unique antigen at the surface of infected erythrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…The exposure to Aedes bites was associated with the evolution of IgG response to Pf Schz and Pf GLURP-R0, while Anopheles exposure was not found to modulate anti- Plasmodium immunity in the 6-week follow-up period. It is increasingly recognized that the immune modulatory properties of mosquito saliva act both on the innate and adaptive immune responses of the vertebrate host, but only a few studies have assessed the consequences of Plasmodium immune responses in a natural population [ 14 , 32 , 33 , 65 ]. These studies investigated the immune relationship within a homologous malaria context ( Anopheles – Plasmodium ), while in the present study, we observed different anti- Plasmodium immunity modulation according to the mosquito genus with a significant effect of Aedes exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations